Investigation on acidity-forming ions in wet and dry deposition during the winter season 1984/85. Untersuchung saeurebildender Ionen in feuchten und trockenen Depositionen im Winterhalbjahr 1984/85 - "Paffrath, M" (1986)
The concentrations of the most important acidity-controlling ions namely sulphate, nitrate, chloride, H/sup +/ and ammonia were measured systematically in rain, snow, frog and dry depositions in Oberpfaffenhofen and Seefeld between September 1984 and February 1985. The measuring methods are described. The results of the ion concentrations and deposition rates are compared, correlations with the wind direction investigated and discussed. With 29 figs., 26 refs.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "ACID RAIN"; "DEPOSITION"; "AIR POLLUTION"; "AMMONIA"; "ATMOSPHERIC PRECIPITATIONS"; "CHLORIDES"; "NITRATES"; "SEASONAL VARIATIONS"; "SULFATES"; "CHLORINE COMPOUNDS"; "HALIDES"; "HALOGEN COMPOUNDS"; "HYDRIDES"; "HYDROGEN COMPOUNDS"; "NITROGEN COMPOUNDS"; "NITROGEN HYDRIDES"; "OXYGEN COMPOUNDS"; "POLLUTION"; "RAIN"; "SULFUR COMPOUNDS"; "VARIATIONS"; "500200* - Environment, Atmospheric- Chemicals Monitoring & Transport- (-1989)"